Deskripsi Kebutuhan Guru dan Siswa Terhadap Media Pembelajaran Fisika - Vina Tri Utami; Neneng Arini; Hadma Yuliani; Nadia Azizah (Universitas Hamzanwadi, 2022)
Description of the needs of teachers and students is one of the information services to describe a state of learning in the classroom. This study aims to determine the physics learning process regarding (1) obstacles in learning, (2) understanding of the material, (3) the use of teaching materials, (4) the use of learning media, (5) a description of the need for media use. This research was conducted by interviewing physics teachers at MAN 2 Pulang Pisau and distributing offline to students in class XI MIA I and XI MIA II. Each class is 20 so that the sample used is 40 students. The method used in this research is a combination of qualitative and quantitative descriptive (Mixed Methods). The data analysis technique used is a qualitative analysis in the form of interviews and a quantitative stage in the form of a questionnaire. The results of the study: (1) obstacles in learning according to teachers and students, namely it is difficult to understand the learning material because there are too many similarities (87.5%); (2) Teachers and students said students had more difficulty understanding static fluid material compared to other materials (90%), (3) teaching materials used according to teachers and students in learning were in the form of textbooks (92.5%), (4) Teachers say they never use learning media, while students use learning media only in the form of worksheets (87.5%), (5) Teachers and students say they really need print media in the form of comic-based media this is to make it easier to understand the material and be motivated in learning ( 97.5%).